Pengaruh Social Media Marketing Terhadap Minat Beli Di Fortunate Coffee Cemara Asri Deli Serdang - Saddha Yohandi; Yuliana; Arwin; Lisa; Ivone (Yayasan Literasi Sains Indonesia, 2022)
Along with the technology that continues to develop until now, it can be seen in ancient times direct buying and selling transactions, but now people and business people are starting to switch to virtual markets and are used to transactions either selling, buying or marketing products. The tactics and strategies used by many business people use social media as a place to market their products or services which is also known as social media marketing which has proven to be very real in increasing sales. The purpose of this study was to determine whether there was an effect of social media marketing on purchase intention at Fortune Coffee Cemara Asri, Deli Serdang. The sample of this research is 60 customers, by using accidental sampling technique. Data analysis used simple linear regression test, while data processing used SPSS. The results of the correlation test between social media marketing and purchase intention of 0.660 means that it has a strong relationship. The results of a simple linear regression test show the results of Y = 8,648 + 0,476 X, which means that every increase or increase of 1 social media marketing unit will increase purchase intention by 0,467 times. Test results the coefficient of determination between social media marketing has a 43.6% relationship with purchase intention, while the remaining 56.4% is influenced by other variables not examined by researchers.